Highly sensitive and fast-response ethanol sensing of porous Co3O4 hollow polyhedra via palladium reined spillover effect. Issue 11 (28th February 2022) - Yuan, Guotao; Zhong, Yihong; Chen, Yufeng; Zhuo, Qiqi; Sun, Xuhui
Abstract : Pd/Co3 O4 HP was developed by simple pyrolysis of Pd doped MOF, which achieved high sensitivity with fast response (12 s)/recovery speed (25 s) for 100 ppm ethanol. APXPS results provide experimental evidence to enhance performance by Pd spillover effect. Abstract : Highly sensitive and fast detection of volatile organic compounds (VOCs) in industrial and living environments is an urgent need. The combination of distinctive structure and noble metal modification is an important strategy to achieve high-performance gas sensing materials. In addition, it is urgent to clarify the chemical state and function of noble metals on the surface of the sensing material during the actual sensing process. In this work, Pd modified Co3 O4 hollow polyhedral (Pd/Co3 O4 HP) is developed through one-step pyrolysis of a Pd doped MOF precursor. At an operating temperature of 150 °C, the Pd/Co3 O4 HP gas sensor can achieve 1.6 times higher sensitivity than that of Co3 O4 HP along with fast response (12 s) and recovery speed (25 s) for 100 ppm ethanol vapor. Near-ambient pressure X-ray photoelectron spectroscopy (NAPXPS) was used to monitor the dynamic changes in the surface state of Pd/Co3 O4 HP. The NAPXPS results reveal that the oxidation and reduction of Pd in the ethanol sensing process are attributed to a spillover effect of oxygen and ethanol, respectively. This work opens up an effective approach to investigate spillover effects in a sensing mechanism of noble metal modified oxide semiconductor sensors.